Anesthesia management of a patient with giant goiter, multiple metastases, and airway stenosis: a case report - Liuxu Yao; Junbiao Fang; Yiyang Hu; Weiying Xie; Wen Zhai (Frontiers in Medicine, 2026)
Patients with giant papillary thyroid carcinoma (PTC) and extensive metastases involving the anterior mediastinum and both lungs face a high risk of severe airway obstruction and ventilation difficulties during anesthesia induction. We report an 18-year-old female with a giant PTC causing critical tracheal compression and extensive metastases. Awake fiberoptic intubation was successfully performed while maintaining spontaneous ventilation. Total thyroidectomy combined with thoracotomy lasted for 10 h, and the blood loss during the operation was about 4,500 mL. After operation, the patient was successfully extubated, and no immediate respiratory complications occurred. However, complications such as acute respiratory distress syndrome (ARDS), acute kidney injury and tracheal fistula occurred in the follow-up treatment. After comprehensive treatment, the patient recovered and was discharged two months later. This case highlights that meticulous perioperative management can provide a safe and effective approach for patients with giant thyroid tumors, extensive mediastinal and pulmonary metastases, and compromised airway integrity.